SISTEM SAPAAN BAHASA MELAYU RIAU ISOLEK PELALAWAN KABUPATEN PELALAWAN - Ririt Hariyanti; Hermandra Hermandra; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study describes the use of, or the use of the Malay language greeting system isolects Palalawan. The aim of this study was to describe the use or consumption of kinship and nonkekerabatan address system in the language of the Malaysian isolects Palalawan Pelalawan. This type of research is qualitative research with a descriptive method, it means analyzing and describing data descriptively. Sources of this research data from some informants from the Pelalawan community. The result of the research is the classification of the greetings system of kinship and nonkekerabatan in the community of Pelalawan Village. by identifying the data, classifying data based on kinship and nonkekerabatan, and describing data in accordance with the study's theory related to the research. Based on the results of the study, the authors found sixty-nine data use or used the greeting system. With the distribution of the data kin and thirty-four thirty-five nonkekerabatan among others by age there are thirteen of the data, greeting by religious titles are four pieces of data, based on nicknames or physical address there are five dates, the greeting to the profession or usual title, there are five dates. And the greeting-shaped word-greeting class there are seven data. Regards isolects Pelalawan Riau Malay language is a form of greeting documentation in Palalawan society in Pelalawan.Keywords: Malay language, salute system, kinship, unrelatedness